2012
DOI: 10.1530/joe-12-0379
|View full text |Cite
|
Sign up to set email alerts
|

11β-Hydroxysteroid dehydrogenase type 2 in zebrafish brain: a functional role in hypothalamus-pituitary-interrenal axis regulation

Abstract: The type 2, 11b-hydroxysteroid dehydrogenase (Hsd11b2) converts active glucocorticoids to their inactive derivatives (e.g. cortisol to cortisone). In most vertebrates, Hsd11b2 is essential for conferring aldosterone-specific actions in mineralocorticoid target tissues and for protecting glucocorticoid-sensitive tissues during stress. However, teleosts do not synthesize aldosterone, and the function of Hsd11b2 is poorly defined. The distribution of Hsd11b2 in nonmammalian brain is also largely unexplored. We te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
50
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(59 citation statements)
references
References 37 publications
9
50
0
Order By: Relevance
“…In this regard, the hypothesis that LRDs will alter gill ionoregulatory elements can be accepted, but in this study, these changes do not impact overall salt and water balance. The view that LRDs can alter cortisol metabolism is consistent with Alderman and Vijayan (2012) who showed that 18βGA decreased 11β-HSD2 activity and elevated whole body cortisol levels in zebrafish. The latter may have been influenced by LRD-induced corticosteroid-mediated events in ionoregulatory tissues of fishes in part due to changes in circulating cortisol levels.…”
Section: Genesupporting
confidence: 80%
See 1 more Smart Citation
“…In this regard, the hypothesis that LRDs will alter gill ionoregulatory elements can be accepted, but in this study, these changes do not impact overall salt and water balance. The view that LRDs can alter cortisol metabolism is consistent with Alderman and Vijayan (2012) who showed that 18βGA decreased 11β-HSD2 activity and elevated whole body cortisol levels in zebrafish. The latter may have been influenced by LRD-induced corticosteroid-mediated events in ionoregulatory tissues of fishes in part due to changes in circulating cortisol levels.…”
Section: Genesupporting
confidence: 80%
“…Nevertheless, 18βGA has been reported to potentiate aldosterone-mediated active Na + transport (uptake) across frog skin (Ishikawa and Saito, 1980), and more recently Alderman and Vijayan (2012) have reported that in zebrafish 18βGA decreased brain 11β-HSD2 activity with an associated increase in whole body cortisol levels. This suggested that 11β-HSD2 can potentially affect the negative feedback loop of corticosteroid synthesis in zebrafish.…”
Section: Introductionmentioning
confidence: 99%
“…The lower 11βhsd2 transcript level may result in higher cortisol availability; we interpret these results combined as a search for a new balance in cortisol action under chronic stress conditions. Promotor analysis in zebrafish revealed putative sites for cortisol-mediated regulation of transcription of 11βhsd2 and (chemical) inhibition of 11βhsd2 activity resulted in increased POA crf expression and elevated cortisol levels (Alderman and Vijayan, 2012). Taken together, these findings indicate a pivotal role for 11βhsd2 in negative feedback control of the stress axis.…”
Section: Poamentioning
confidence: 82%
“…While the mechanism(s) is unclear, a recent study suggested a role for ATP-binding cassette transporters in the rapid cortisol clearance in threespine stickleback ( Gasterosteus aculeatus ) embryos40. Another possibility is the enzyme 11βHSD2, which converts cortisol to inactive cortisone and contains putative glucocorticoid response elements (GRE) in its promoter region41. This enzyme plays a role in countering exposure to cortisol excess in zebrafish ovarian follicles5, but its role in embryos remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%